Factors influencing customer selection of omni-channel supermarket retailing: An empirical study in Sri Lanka - Hiruni Poornima Maheepala; Achini Ann Malinthi Jayawardena; D.G.N.D. Jayarathna (Journal of Sustainable Development of Transport and Logistics, 2024)
Purpose: This study aims to identify the factors affecting and impacting the Omni channel selection of customers in supermarket retailing, addressing a research gap in this area. Methodology: The researcher conducted an empirical study using a questionnaire distributed among 384 supermarket customers. Factor and regression analyses were performed to determine the influential factors. Results: The study found that risk management, experience and expected performance, security aspects, and customer compatibilities have individual effects on customer Omni channel selection. Additionally, recommendations were made to enhance the value of existing or future Omni channel supply chains. Theoretical contribution: This research contributes to the understanding of customer behavior in Omni-channel supermarket retailing, particularly in the context of a developing country like Sri Lanka. The findings can inform both academic and practical discussions on supply chain management and e-commerce. Practical implications: The study's recommendations can guide supermarket retailers in improving their Omni-channel strategies, ultimately enhancing customer satisfaction and loyalty. This, in turn, can positively impact the retail industry and the broader economy of Sri Lanka.